Announcements (The Review of Asset Pricing Studies, 2017)
Journal Article Announcements Get access The Review of Asset Pricing Studies, Volume 7, Issue 1, June 2017, Page 1, https://doi.org/10.1093/rapstu/rax013 Published: 12 May 2017